الاحتياجات التدريبية لمديري المدارس الابتدائية بمدينة مكة المكرمة في ضوء التعليم عن بعد - المطرفي، خالد بن فيصل; الحارثي، عبدالله بن ضيف الله محمد (جامعة الأميرة نورة بنت عبد الرحمن - كلية التربية, 2023)
هدفت الدراسة إلى الكشف عن الاحتياجات التدريبية لمديري المدارس الابتدائية بمدينة مكة المكرمة في ضوء التعليم عن بعد، والكشف عن دلالة الفروق في استجابات عينة الدراسة تعزى لاختلاف المؤهل العلمي وسنوات الخبرة الإدارية وعدد الدورات التدريبية في مجال التعليم عن بعد. واعتمدت الدراسة على المنهج الوصفي المسحي. وتم تطبيق استبانة على جميع مديري المدارس الابتدائية في مدينة مكة المكرمة باستخدام أسلوب الحصر الشامل، وقد استجاب منهم (137) مدير مدرسة. وأظهرت النتائج أن الاحتياجات التدريبية لمديري المدارس الابتدائية بمدينة مكة المكرمة في ضوء التعليم عن بعد جاءت بدرجة عالية، بمتوسط حسابي (3.99). وجاءت الاحتياجات التدريبية في مجال المعارف في المقدمة، يليها مجال المهارات، وأخيرا مجال الاتجاهات. وتمثلت أكبر الاحتياجات التدريبية في مجال المعارف في معرفة الأنظمة واللوائح التي تحكم التعليم عن بعد، ومعرفة طرق تقويم أداء المعلمين المناسبة للتعليم عن بعد. وتمثلت أكبر الاحتياجات التدريبية في مجال المهارات في زيادة مهارات مديري المدارس في تنفيذ الخطة المدرسية أثناء عملية التعليم عن بعد. وتمثلت أكبر الاحتياجات التدريبية في مجال الاتجاهات في اعتقاد المديرين في: أن التعليم الحضوري أكثر فاعلية وفائدة للطلبة. كما أظهرت عدم وجود فروق دالة إحصائيا بين متوسطات استجابات مديري المدارس تعزى لاختلاف المؤهل العلمي، بينما وجدت فروق تعزى لاختلاف سنوات الخبرة في اتجاه مديري المدارس الذين لديهم خبرات أقل من 5 سنوات والذين لديهم من (5 -10) سنوات. كما وجدت فروق تعزى لاختلاف الدورات التدريبية في التعليم عن بعد في اتجاه مديري المدارس الذين لا يمتلكون دورات تدريبية والذين لديهم من دورة إلى ثلاث دورات تدريبية. The current study aimed at identifying the training needs of primary school principals in Makkah Al-Mukarramah in light of distance learning. It also sought to reveal the significance difference in the responses of the study sample due to differences in academic qualifications, years of administrative experience, and the number of training courses completed in the domain of distance learning. To achieve the goals of the study, the study followed the descriptive analytical approach and used the comprehensive inventory method in developing and administering a questionnaire to all principals of primary schools in Makkah Al Mukarramah, and a total of 137 principals from the study sample responded. The results of the study showed that the training needs for primary school principals in Makkah Al-Mukarramah in relation to distance learning scored high, with an average score of (3.99). Training needs in the domain of knowledge came first among the other needs, followed by the training needs related to skills, and finally the training needs related to orientations and opinion. Knowing the rules and regulations related to distance learning came as the greatest training needs in the domain of knowledge, as well as knowing the appropriate methods for evaluating teachers' performance in distance learning. In the domain of skills, developing the skills of principals in implementing the school plan during the distance learning process were among the greatest training needs. With regards to orientations and opinions, the greatest training needs were related to the principals’ existing belief that the presence of students in the classroom is more effective and beneficial than distance learning. The study also reported that there are no statistically significant differences between the averages of school principals’ responses due to differences in academic qualifications, but there are differences in relation to years of experience in favour of school principals who have less than 5 years of experience and those who have (5 -10) years of experience. There are also statistical differences in the different training courses on distance learning in favour of school principals who did not take training courses and those who took at least one and three training courses.
Keywords: التعليم الإلكتروني -- مديرو المدارس -- البرامج التدريبية -- السعودية